Morphological Characterization of the Medial Plantar Longitudinal Arch Foot in a Chilean Population [Caracterización Morfológica del Arco Plantar Longitudinal Medial del Pie en Una Población Chilena] - Sanchez-Ramirez, C (Universidad de la Frontera, 2017)
The (MPLA) is the most important component in statics and dynamics of the vault plant. Its height defines normal, flat and cavus feet, which are predisposing factors for injuries. The objective of this research was to describe and relate in a population of Chilean university students the prevalence of normal, cavus and flat feet according to body-mass index (BMI), sex, and weekly physical activity (PA) and the distribution of asymmetries between feet. 209 subject were studied (128 men and 81 women), university students, whose age, height, weight and BMI was of 20.4 years (±3.4); 1,68 m (±0.09); 67.6 kg (±12.4) and 23.77 (±3.0) respectively. The PAs habits of the sample were determined by means of questionnaire. The footprint is obtained by photo-podoscopy, which was evaluated by the Arch Index (AI) of Cavanagh and Rodgers. Men have higher prevalence of flat foot (31.3% against 11.1%). There are both statistically significant positive correlations between AI and BMI in both sexes. Greater correlation between left AI and PA in both men and women was obtained with statistical significance. The 31.25% of men and 37.04% of women presented asymmetries in MPLA. Men with normal BMI have 64.20% of asymmetric feet. Women that practice between 6 and 10 hours of PA a week presented 50.98% of asymmetric feet. The BMI is related to a decrease of the height of MPLA, suggesting the control of this variable in subjects with flexible flat foot and valgus flat foot diagnosis. The practice of PA is related to the height of the MPLA increased in men and women and it is known that it also helps to reduce BMI, acting in accordance to these two variables. © 2017, Universidad de la Frontera. All rights reserved.